MANAJEMEN PENDIDIKAN ISLAM DI PONDOK PESANTREN: STRATEGI INTEGRASI NILAI-NILAI KEISLAMAN DALAM KURIKULUM - Wahyudi Widodo (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2023)
This study examines the strategic integration of Islamic values into the curriculum of Islamic boarding schools (pondok pesantren). It explores the challenges posed by modernization and globalization, necessitating innovative educational management to maintain the relevance of pesantren while preserving their Islamic identity. Using a qualitative descriptive method and a case study approach, the research investigates the integration of Islamic values into formal and non-formal curricula through interviews, observations, and document analysis. Findings highlight that pesantren integrate values such as honesty, discipline, and Islamic etiquette into everyday life and formal lessons. The study underscores the crucial role of kiai (spiritual leaders), ustaz (teachers), and pesantren managers in fostering these values. The research concludes with recommendations for holistic and adaptive strategies to sustain the integration of Islamic values, ensuring the educational outcomes align with Islamic principles while addressing contemporary needs